2021
DOI: 10.5114/hpc.2021.110112
|View full text |Cite
|
Sign up to set email alerts
|

Can behavioral interventions increase physical activity in youth with cerebral palsy? A scoping review

Abstract: Authors' contributionWkład autorów: A. Study design/planning zaplanowanie badań B. Data collection/entry zebranie danych C. Data analysis/statistics dane -analiza i statystyki D. Data interpretation interpretacja danych E. Preparation of manuscript przygotowanie artykułu F. Literature analysis/search wyszukiwanie i analiza literatury G. Funds collection zebranie funduszy SummaryThe primary goal of adaptive physical and special education is to increase the participation of individuals with special motor needs i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
(55 reference statements)
0
1
0
Order By: Relevance
“…Therefore, an attempt to use a tool for developing communication skills may have a cross-influence on communication and overall physical activity level. Literature reviews conducted by our research group and others have indicated that behavioral interventions can increase physical activity in youths with intellectual disability [5,6]. In addition to behavioral interventions, the approaches using communication therapy can yield similar cross-efficacy for communication and physical activity.…”
Section: Introductionmentioning
confidence: 89%
“…Therefore, an attempt to use a tool for developing communication skills may have a cross-influence on communication and overall physical activity level. Literature reviews conducted by our research group and others have indicated that behavioral interventions can increase physical activity in youths with intellectual disability [5,6]. In addition to behavioral interventions, the approaches using communication therapy can yield similar cross-efficacy for communication and physical activity.…”
Section: Introductionmentioning
confidence: 89%